1984
DOI: 10.1002/ss.37119842703
|View full text |Cite
|
Sign up to set email alerts
|

Student paraprofessionals within student affairs: The state of the art

Abstract: The utilization of undergraduate students as peer helpers within institutions of higher education can be traced to the early history of American colleges and universities. As Materniak points out in Chapter Two, student tutors have been assisting their peers since the colonial period. Powell and others (1969) cite the use of students in residence halls as resident assistants, proctors, hall counselors, and advisors since the turn of the century. Although these early efforts were primarily informal and unsyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…(Because data were requested only from student affairs divisions, there is a high probability that study skillstutorial programs and academic advising programs are underrepresented, because on many campuses these programs are administratively housed in academic affairs divisions or departments. A more detailed treatment of comparisons of these data with earlier studies may be found in Ender [1984]. )…”
Section: Extent Of Student Paraprofessional Programsmentioning
confidence: 93%
See 1 more Smart Citation
“…(Because data were requested only from student affairs divisions, there is a high probability that study skillstutorial programs and academic advising programs are underrepresented, because on many campuses these programs are administratively housed in academic affairs divisions or departments. A more detailed treatment of comparisons of these data with earlier studies may be found in Ender [1984]. )…”
Section: Extent Of Student Paraprofessional Programsmentioning
confidence: 93%
“…Given what is known about the unreliability of these selection methods (Ostroth, 1981), however, new approaches seem worth trying. One approach (Ender, 1983(Ender, , 1984Ender & McFadden, 1980;Upcraft & Pilato, 1982) involves training paraprofessionals before making selection decisions. During training one can get a much more accurate picture of a potential paraprofessional's skills, knowledge, personality, and style-ah factors critical to success in most programs-before making a selection decision.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Thtors are " ... students who have been selected and trained to offer educational services to their peers. " (Ender, 1984;Maxwell, 1979). A tutor is simply defmed as" ...a person who gives individual instruction."…”
mentioning
confidence: 96%
“…The use of peers, sometimes referred to as "paraprofessionals," in teaching and learning is not itself a recent phenomenon in higher education. Various roles, such as undergraduate teaching assistants, peer tutors, resident assistants, and orientation leaders proliferate on college and university campuses (Ender, 1984;Ender & Newton, 2000).…”
Section: Educational Benefits Of Student Employmentmentioning
confidence: 99%
“…The rationales behind supporting students in these roles include cost effectiveness (Boud, 2001a;Miller, Groccia, & Miller, 2001;Topping, 1996) as well as research indicating that students may learn best through interaction with other students (Astin, 1993;Ender, 1984;Topping). According to Miller, Groccia, and Miller, peers play influential learning roles for each other:…”
Section: Educational Benefits Of Student Employmentmentioning
confidence: 99%